IMPACT OF PSYCHOLOGICAL VARIABLES ON THE COMMUNITYBASED FLOODPLAIN WETLANDS (BEELS) FISHERIES MANAGEMENT PRACTICES - BARMAN, R. C.; VASUDEVAPPA, C.; KAR, DEVASHISH; DANA, S. S. (Journal of the Inland Fisheries Society of India, 2021)
A study was conducted in four wetlands (Beels) of Assam to assess the impact of two psychological predictor variables namely ‘management capabilities of Beel Development Committee, X1 and ‘involvement of NGOs’ X2 on ‘knowledge levels of Beel users’ on community-based fisheries management’Y. The study revealed that both the predictor variables X1 and X2 were significantly (r =0.21** and 0.49** respectively) associated (P<0.01) with knowledge levels of Beel users on community-based fisheries management (Y). Moreover, between these two variables, involvement of NGOs (X2 ) was found to be the most significantly contributing variable on the dependent variable (Y). Key words: Floodplain wetland, Beel, community-based fisheries management, NGO.